A Study Case on Noise Pollution to the Residential Areas Along Jalan Kluang, Batu Pahat, Johor - Abdul Rahim, Muhamad Haffiz; Yean Ghing , Tong (Recent Trends in Civil Engineering and Built Environment, 2024)
In recent year, noise pollution has become a common environmental problem, especially in developing cities. It is one of the most significant urban environmental issues affecting people’s daily life and health. The aim of the study are to identify the factors and effects of noise pollution in residential area along Jalan Kluang and evaluate the acoustic comfort of the resident areas. The residential areas located near to heavy traffic road of Jalan Kluang including Taman Pura Kencana, Taman Gading 1, and Taman University were chosen in this study. Questionnaire has been developed based on the literature review. Expert reviews have been carried before distributing to the respondents. Total number of respondents that have been collected were 72 respondents. The results showed that the main factors of noise pollution in the residential area are noise that produced from construction activities, inside the house, nearby neighbourhood, and traffic road. From the survey, noise from the neighbourhood nearby recoded the highest means score of at 4.40 using 5 Likert scale which was obtained from respondents living in Taman Universiti. For the effect of noise pollution, the highest data that has been collected was sleep disturbance at Taman Universiti which obtained the mean value of 4.40. The study the acoustic comfort of the respondents in their residential areas was considered good.